MENINGKATKAN MINAT BELAJAR SISWA DENGAN MICROSOFT EXEL PADA MATA PELAJARAN FISIKA MATERI HUKUM HOOKE - SRI ISWATI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2022)
This Classroom Action Research aims to increase students' interest in learning by using Microsoft Excel in the subject of Physics subject to Hooke's Law. The research was conducted in two cycles, each cycle consisting of four stages: planning, action, observation and reflection. The research subjects were students of class XI IPA 1 at SMAN 1 Tegalombo for the 2022-2023 academic year, a total of 33 students. Data collection techniques using questionnaires, direct observation and written tests. In this study there are three indicators of interest, namely feelings of pleasure, feeling useful and students' desire to use Microsoft Excel. Based on the data analysis, it can be concluded that the use of Microsoft Exel in the Subject of Physics Material on Hooke's Law Class XI IPA 1 SMA Negeri 1 Tegalombo, Pacitan Regency, Academic Year 2022/2023, can increase students' interest in learning. Student interest in learning from 83.08% in cycle 1 to 98.23% in cycle 2. There was an increase of 15.15%. The average score for individual student creativity for cycle 1 was 63.09%, and for cycle 2 it increased to 96.40%, while the test scores before the action were 50.61. In cycle 1, the average student score increased but was not optimal, still in the